Comparison of the effect of audiovisual and verbal instructions on patient performance while performing automated Humphrey visual field testing - Devendra Maheshwari; Aditi Nair; Techi Dodum Tara; Neelam Pawar; Rengappa Ramakrishnan; D Ranitha Guna Selvi; Mohammed Sithiq Uduman (Indian Journal of Ophthalmology, 2023)
Purpose: To compare the effect of audiovisual and verbal instructions on patient performance while performing automated Humphrey visual field testing. Methods: This was a prospective study. A total 120 patients divided into groups of 40 each were recruited from the glaucoma outpatient department (OPD). All patients were aged 35–75 years with no previous experience of performing HFA. Patients with hearing impairment, any other cognitive impairment, and best-corrected visual acuity (BCVA) ≤6/36 on Snellen's visual acuity were excluded. The first two groups were given strict (conservative) and lenient (liberal) verbal instructions. The instructions were adapted from those listed in the manufacturer's instruction. and the third group was shown a standard video depicting in detail how perimetry was to be performed. A questionnaire was given to each patient before and after the test to assess the patient's performance. Results: Patients diagnosed with glaucoma during testing in each group were 29 (72.50%), 30 (75.0%), and 33 (82.5%) in the video instructed, strictly verbal, and leniently verbal groups, respectively. The overall mean deviation (MD) in the right eye (RE) was of − 3.38 (−4.9 to 1.9) and in the left eye (LE) was − 3.96 (−6.4 to − 1.9). Reliable field was slightly higher for the video instructed group (47.5%) and lowest for the strictly verbal group (22.5%) (P = 0.033). A higher number of patients were very motivated in the video instructed group (27%) (P = 0.041). Post-test questionnaires showed that 40% of patients felt they have performed the test with 100% accuracy in video group with less guessing. A higher number of patients in the video instructed group (85%) felt instruction was helpful in performing the test (P = 0.001). Conclusion: The video groups were more motivated and had better confidence to perform the test with less anxiety and stress and with probably better understanding of the procedure due to visual effects enhancing their understanding.